Composição químico-bromatológica e avaliação sensorial de silagens de capim elefante Pennisetum purpureum, Schum. com níveis de resíduos da acerola e tamarindo - Maia, Isaac Sydney Alves da Silva (2015)
The objective of this study was to evaluate the nutritional value of elephant grass silages with 33 the addition of residue of acerola. The design was completely randomized in five levels of 34 inclusion, 0; 5; 10; 15 and 20%, with four replications. The silos were opened with 90 days and 35 made the evaluations of NH3-N, sensorial analysis, pH, samples for chemical-bromatological 36 analysis and determination of the TDN. The DM, OM and EE were elevated in .54; .16 and .03 37 percentage points, respectively, for each 1% inclusion of the residue. The TC and pH presented 38 mean value respective 84.2% and 3.97, the pH was within the range to well preserved silage. 39 The NDF and HCEL have obtained reductions of 2.19 and 5.96% levels of 0-20% inclusion, 40 respectively. While elevations .19% for the ADF and .29% for the LIG every 1% waste 41 addition. The cellulose and TDN were presented minimum point of 12.5% inclusion and their 42 levels of 41.35 and 51.43%. To CP, IPND and IPAD, there were increases of 0.13% for each 43 1% inclusion of the residue for the three parameters. The TDN has presented minimum point 44 of 51.43% to the level of 12.4% inclusion. The N-NH3 of silages ranged from .47 to .79% from 45 levels 0-20% of inclusion of acerola. All silages were classified as "good to very good" 46 according to the nutritional and organoleptic characteristics. It is concluded that addition of the 47 acerola residue improved the nutritive value of silage fermentation characteristics evaluated 48 keeping their may be added to the 20% level